Adherence to oral anticancer agents: Healthcare providers' perceptions, beliefs and shared decision making in Belgium and the Netherlands. (2nd April 2016) - Verbrugghe, Mathieu; Timmers, Lonneke; Boons, Christel C.L.M.; Van Den Bemt, Bart J.F.; Hugtenburg, Jacqueline G.; Van Hecke, Ann
Abstract: Background Little is known about healthcare providers' (HCPs) perceptions of adherence management of oral anticancer agents (OACA). The study aims to explore HCPs perceptions of OACA and adherence. Methods A cross-sectional, multi-center observational study among HCPs in hemato-oncology settings in Belgium and the Netherlands was conducted. Physicians, nurse practitioners, nurses and pharmacists were asked to complete questionnaires on their perception of patient adherence and its management (PAMQ) and their beliefs about OACA (BMQ-Specific). Physicians were also asked to complete a questionnaire on their perception of shared decision making (SDM-Q-Doc). Results The sample consisted of 254 HCPs. Variations were found between HCPs on the PAMQ: 56%, 50%, 28% and 23% of, respectively, physicians, nurse practitioners, nurses and pharmacists reported to know the level of adherence of their patients and 59%, 53%, 43% and 10% of, respectively, physicians, nurse practitioners, nurses and pharmacists think that patients discuss adherence with them. 70%, 82%, 63% and 62% of, respectively, physicians, nurse practitioners, nurses and pharmacists reported to have knowledge of causes of non-adherence, while 78%, 87%, 76% and 80% of them reported to have knowledge of consequences of non-adherence. 81%, 92%, 83% and 67% of, respectively, physicians, nurse practitioners, nurses and pharmacists felt able to influence adherence. Lower concerns beliefs were associated with a higher total score on the PAMQ [β (SE)=−0.85 (0.24); CI −1.33–−0.38]. Physicians scored a mean of 75 on the SDM-scale. Conclusions A considerable part of the HCPs states they do not know the adherence of their patients, nor do they think patients discuss adherence with them. However, they feel to have knowledge of adherence and perceive to be able to influence adherence of their patients.